La magia y los juegos de azar en los Reales Mineros Novohispanos - Eduardo Flores Clair (Nuevo mundo - Mundos Nuevos, 2016)
This research addresses the problems related to gambling in the New Spain mining cities. We refer, in great lines, to the characteristics of working conditions in relation to the good luck in finding rich minerals. We also deal with amusements, pastimes, and dedicated time to leisure. We study the passion that gambling generated and the existence of gambling houses, considering the owners and customers. Finally yet importantly, some magic charms to get good luck and wishes through dreams practices also are discussed.